Technology, Artificial Intelligence, and Robotics in Future Wars - Oran, İbrahim Bora; Yilmaz, Sait; Ertürk, Muzaffer; Gün, Hüseyin (Journal of Organizational Behavior Research, 2023)
This study aims to show the importance of initiating studies on the role of intelligence and its new uses in future wars without further delay and also to contribute to closing the current gap in this subject in the literature. This study aims to analyze the future post-modern wars through the reciprocal interoperability and multi-integration of technology and intelligence. This study, which adopts a qualitative research methodology, will primarily benefit from secondary data sources such as scientific books and articles in addition to scientific data analysis methods such as document and content analysis and interpretation. This study significantly contributes to the role of intelligence and the necessity to promote new scientific studies and to end the present gap in the data without delay. The ongoing developments taking place in technology will bring about the transformations clarified in this study. Ideas will be generated regarding the expected developments in technology and their roles on the battlefields of future wars. The scope of this study is the increasing importance and role of intelligence in developing network technologies as well as the potential areas where autonomous systems which can understand machinery can be used.